Социолингвистическая ситуация в г. Висaгинасе - Мирославовна Коницкая, Мария (Slavistica Vilnensis, 2009)
The purpose of this article is to describe the sociolinguistic situation in Visaginas, a small town in Lithuania on the border of the Baltic-Slavic areal. Founded in 1975, the town was created in the middle of a Polish-speaking area where Russian became the dominant language. In the last thirty years after the collapse of the Soviet Union and the emergence of the independent Republic of Lithuania, the situation has changed due to several waves of migration. At present the ethnic composition of the town comprises around forty ethnic groups. The author argues that the sociolinguistic situation in Visaginas will be changing rapidly in the nearest future.